2016
DOI: 10.1007/s10856-016-5725-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations during processing and in vitro degradation of porous calcium polyphosphates

Abstract: A 2-Step sinter/anneal treatment has been reported previously for forming porous CPP as biodegradable bone substitutes [9]. During the 2-Step annealing treatment, the heat treatment used strongly affected the rate of CPP degradation in vitro. In the present study, x-ray diffraction and (31)P solid state nuclear magnetic resonance were used to determine the phases that formed using different heat treating processes. The effect of in vitro degradation (in PBS at 37 °C, pH 7.1 or 4.5) was also studied. During CPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Unfortunately, due to overlapping of the stronger α‐CPP peaks (at 2 θ ≈ 25+ and 32°) unique identification of α ‐CPP by XRD is not possible. As reported elsewhere in a study in which more sensitive XRD methods and 31 P MAS NMR were used to analyze as‐made porous bulk FD‐ and SD‐CPP samples, the SD‐CPP was shown to be β‐CPP only while FD‐CPP indicated a multiphase structure consisting of β‐CPP and significant amounts of α‐CPP as well as traces of ultraphosphates and amorphous CPP …”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Unfortunately, due to overlapping of the stronger α‐CPP peaks (at 2 θ ≈ 25+ and 32°) unique identification of α ‐CPP by XRD is not possible. As reported elsewhere in a study in which more sensitive XRD methods and 31 P MAS NMR were used to analyze as‐made porous bulk FD‐ and SD‐CPP samples, the SD‐CPP was shown to be β‐CPP only while FD‐CPP indicated a multiphase structure consisting of β‐CPP and significant amounts of α‐CPP as well as traces of ultraphosphates and amorphous CPP …”
Section: Resultssupporting
confidence: 54%
“…In an earlier study of bone formation in critical size defects created in rat calvaria and filled with 150–250 μm amorphous CPP powders for a 1‐month period, new bone formation was not observed. One possible reason for this lack of new bone forming was the too rapid degradation of the amorphous CPP, a characteristic noted in later in vitro experiments . These in vitro degradation studies, also demonstrated dramatic differences in degradation rates of two grades of CPP particulate formed using the different annealing schedules subsequently used in the in vivo investigation reported herein.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations